A look at youth and adult education: what students say about dropping out and returning to school in the midst of the Covid-19 pandemic (Research, Society and Development, 2022)
Taking as a methodological approach the field research aligned with bibliographic research, this work aims to present a look on the subjects of Youth and Adult Education (YAE) of Elementary School of a municipal school on the western border of Rio Grande do Sul State, facing their situation. It was sought to map the reasons for dropping out of school in times that they should be studying and, at the same time, contextualize the impact of social leave caused by COVID-19 in view of their expectations and longings exactly in a period that they chose to return to school and complete their schooling. From the perspective of Content Analysis, the research data have pointed to the perspectives and longings for the return to classes, just at the moment when the school needs to be closed due to the threat of contagion by COVID-19. The study has shown that the target public of the study does not receive affirmative actions from federal government, having serious difficulties in follow school activities via the Internet due to lack of financial resources. Thus, the research have shown that the subjects of the YAE, when returning to school, face issues already experienced in the past: lack of conditions to maintain the family given the difficulties that the pandemic period puts them, which forces many to abandon their studies again. The remaining ones report being happy with the return to school and see in the physical presence the possibility of further learning, since they are not able to follow the virtual classes due to both financial and time to perform the pedagogical tasks reasons.